2019
DOI: 10.1051/metal/2018096
|View full text |Cite
|
Sign up to set email alerts
|

Study on the behaviour of DS-Class inclusions in advanced bearing steel

Abstract: The source and generated mechanisms of DS-size inclusions in bearing steel were studied by sampling systematically and using ASPEX, SEM and EDS to analyse the morphology, composition and amount of non-metallic inclusions larger than 13 µm. Two kinds of typical DS-size inclusions were found in the refining process: type I is CaO-MgO-Al2O3-SiO2 distributed evenly and wrapped by CaS; type II is composite inclusion with MgO-Al2O3 as the core, CaO-Al2O3 and CaO-SiO2 as the inner layer, covered by CaS. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Metallurgists have conducted significant research on inclusion control in bearing steel [8][9][10][11][12][13][14][15][16][17]. At present, there are two main methods for inclusion control in bearing steel, strong aluminium deoxidation [8][9][10][11][12][13][14][15], and weak siliconmanganese deoxidation [11,16,17]. In strong aluminium deoxidation, the total oxygen content in steel is low and the number of inclusions is small.…”
Section: Introductionmentioning
confidence: 99%
“…Metallurgists have conducted significant research on inclusion control in bearing steel [8][9][10][11][12][13][14][15][16][17]. At present, there are two main methods for inclusion control in bearing steel, strong aluminium deoxidation [8][9][10][11][12][13][14][15], and weak siliconmanganese deoxidation [11,16,17]. In strong aluminium deoxidation, the total oxygen content in steel is low and the number of inclusions is small.…”
Section: Introductionmentioning
confidence: 99%
“…This method has the advantage of relatively complete observation of the appearance and size of the inclusion. In addition, the composition of the inclusion was analyzed by scanning electron microscopy (SEM) [11]. The disadvantage is that the dissolution takes a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, research on DS-type inclusions has mainly focused on bearing steel. Wu et al [14] found two typical DS-type inclusions in the refining process for bearing steel. Type I was CaO-MgO-Al 2 O 3 -SiO 2 uniformly distributed and wrapped by CaS.…”
Section: Introductionmentioning
confidence: 99%